A Maximum Transfer Efficiency Tracking Method for Dynamic Wireless Charging Systems of Electric Vehicles. (23rd November 2021) - Trung, Nguyen Kien; Diep, Nguyen Thi
Abstract : This paper proposes a new control method to improve transfer efficiency for dynamic wireless charging systems of electric vehicles (EVs). In the charging process, the equivalent impedance in the receiving side varies according to the state of charge of the battery system that reduces the transfer efficiency. An impedance control circuit is constructed on the receiving side to track the optimization impedance that transfer efficiency is maximized. However, the optimization impedance depends on the coupling coefficient. Therefore, in this paper, the coupling coefficient, which varies according to the EVs position, is online estimated only from the receiving side. A 1.5 kW dynamic wireless charging system prototype is built in the laboratory environment. In experiment results, the greatest transfer efficiency obtains 94.14% when the EVs move in aligned on the charging lane. Furthermore, the proposed control method improves by 6% on the transfer efficiency in the case of 30% misalignment when the transfer efficiency obtains 91%.